INFORMATIVE-COMMUNICATIVE NATURE OF MASS MEDIA . (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
It is hard to imagine any area of ​​modern society experiencing the process of globalization without the language of the media. The breadth of media opportunities requires an in-depth study of their activities and development, and their impact on the audience. Media science is a new interdisciplinary field based on traditional methods. The formation of the language of the media is closely linked to their common mission. How viewers perceive information also depends on what tool is used to convey it. Each media uses its own language and methods of updating